Phase transfer reaction of potassium superoxide with benzylic methyl and methylene compounds in aprotic medium - Shukla A.K.; Singh K.N. (My University, 2025)
Tetraethylammonium superoxide, generated in situ by the phase transfer reaction of potassium superoxide and tetraethylammonium bromide, brings about an easy oxidation of a variety of benzylic methyl and methylene compounds under significantly mild reaction conditions, at room temperature.